Practices of resistance in the Caribbean: narratives, aesthetics, politics - Beushausen, Wiebke; Brandel, Miriam; Farquharson, Joseph T.; Littschwager, Marius; McPherson, Annika; Roth, Julia (Taylor and Francis, 2018)
Using folklore to challenge contemporary social norms : Papa Bois, Mama D'Lo, and environmentalism in Caribbean literature / Giselle Liza Anatol -- Shadows pass the surface : decolonial (re)configurations of indigenous presence in Merle Collins's The colour of forgetting / Geoffrey MacDonald -- Acts of translanguaging and marooning as forms of resistance in French Caribbean literature / Paula Prescod -- From anti-colonial to anti-modernist fesistance : historiopoetic transformations of the maroon in selected works of Édouard Glissant, Patrick Chamoiseau, and Raphaël Confiant / Sarah Gröning -- Cultures of resistance : dialectical images of the Haitian revolution in Haitian culture and literature / Patrick Eser -- Postcolonial poetics : El reino de este mundo and the resistance of lo real maravilloso / Marius Littschwager -- Caribbean activism for slavery reparations : an overview / Claudia Rauhut -- Debated existences, claimed histories : black indigenous women's diasporic lives in Costa Rica / Christina Schramm -- Una universidad tomada : resistance performances in the (re)construction of spaces of resistance and contention during the first wave of the 2010-2011 University of Puerto Rico student movement / Alessandra Rosa -- Troubling our intersections : a Caribbean feminist methodology as resistance approach / Andrea N. Baldwin and Marva Cossy -- Practices of resistance and cyberfeminism in Cuba / Sandra Abd'Allah-Álvarez Ramírez -- Racism vs. socialism in Cuba : a misplaced conflict (notes on/against internal colonialism) / Roberto Zurbano Torres -- Let us be Moors : conversion to Islam in Cuba / Ilja Labischinski -- Thinking resistance : critique and resistance in the philosophical concepts of Foucault and in the postcolonial and decolonial theories of Bhabha and Mignolo / Marita Rainsborough.
Keywords: Caribbean Area -- Social life and customs; Caribbean Area -- Social conditions